Consequence of Dementia and Cognitive Impairment by Primary Nucleation Pathway - Singh, Aditya; Ansari, Vaseem Ahamad; Ansari, Tarique Mahmood; Hasan, Syed Misabah; Ahsan, Farogh; Singh, Kuldeep; Wasim, Rufaida; Maheshwari, Shubhrat; Ahmad, Asad (Hormone and Metabolic Research, 2023)
An acquired loss of cognition in several cognitive domains that is severe enough to interfere with social or professional functioning is called dementia. As well as a moderately in-depth mental status examination by a clinician to identify impairments in memory, language, attention, visuospatial cognition, such as spatial orientation, executive function, and mood, the diagnosis of dementia requires a history evaluating for cognitive decline and impairment in daily activities, with confirmation from a close friend or family member. The start and organization of the cognitive assessment can be helped by short screening tests for cognitive impairment. Clinical presentations show that neurodegenerative diseases are often incurable because patients permanently lose some types of neurons. It has been determined through an assessment that, at best, our understanding of the underlying processes is still rudimentary, which presents exciting new targets for further study as well as the development of diagnostics and drugs. A growing body of research suggests that they also advance our knowledge of the processes that are probably crucial for maintaining the health and functionality of the brain. We concentrate on a number of the animal models of memory problems that have been mentioned in this review article because dementia has numerous etiologies. Serious neurological impairment and neuronal death are the main features of neurodegenerative illnesses, which are also extremely crippling ailments. The most prevalent neurodegenerative disorders are followed by those primary nucleation pathways responsible for cognitive impairment and dementia.
Keywords: norepinephrine; adrenal; steroid hormones; serotonin; neuroendocrine; neuropeptides